The Path to Convertibility and Growth : The Tunisian Experience - Bell, Gerwin; Duran, Paul.; Nsouli, Saleh; Yucelik, M. (Washington, D.C. : International Monetary Fund, 1993)
This paper charts Tunisia's transformation from an inward-looking, heavily regulated economy into a predominantly market- and export-oriented one. The paper highlights some of the major challenges facing the country and draws lessons from Tunisia's experience that can be useful for other countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet